KARAKTERISTIK KEMANDIRIAN PEDAGANG ECERAN DI DESA KELUAS HULU KABUPATEN MELAWI - Meriyani, Meriyani; S, Bambang Genjik; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this study is the Characteristics of Independency of Retail Traders in Desa Keluas Hulu Kabupaten Melawi. The research aims to know Characteristics of Independency of retail traders. The method used is descriptive of the qualitative study. This research data source was retail merchants and the data is How characteristics emotional independence of retail merchants, Characteristic of independence behavior retailers, Characteristic of independence value retail merchants As well as the results observation and interview With retailer merchant. The result of studies show that the characteristics of the independence of emotional that merchants have are very good, that traders can operate with their ability and can solve problems related to their own business without being dependent on others, and for the self-reliance characteristics of retail behavior are also good, based on how the tradesmen can make decisions according to their ability. The quality of independence is just as good, based on how traders are able to consider or assess possible outcomes of a moral nature and will be able to act on and determine the right choices.Â Keywords: Characteristics of Independency of Retail Traders